2011
DOI: 10.2298/vsp1112041j
|View full text |Cite
|
Sign up to set email alerts
|

Mirasol PRT system inactivation efficacy evaluated in platelet concentrates by bacteria-contamination model

Abstract: Efficient inactivation of investigated bacteria types with a significant CFU depletion in PC-P units was obtained--3 Log for all three tested species, and 5 Log for Escherichia coli. The safety of blood component therapy, primarily the clinical use of PCs can be improved using the Mirasol PRT system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…20 An alternative is the use of pathogen inactivation (PI) techniques. The available systems can be classified into photochemical systems (INTERCEPT), 21,22 photodynamic systems (Mirasol), [23][24][25] and physical techniques (Theraflex). [26][27][28] The purpose of the technologies of PI systems is to prevent bacterial replication.…”
Section: Resultsmentioning
confidence: 99%
“…20 An alternative is the use of pathogen inactivation (PI) techniques. The available systems can be classified into photochemical systems (INTERCEPT), 21,22 photodynamic systems (Mirasol), [23][24][25] and physical techniques (Theraflex). [26][27][28] The purpose of the technologies of PI systems is to prevent bacterial replication.…”
Section: Resultsmentioning
confidence: 99%
“…RF‐PI treatment targets the RNA or DNA of pathogens; however, as PLTs contain mRNA this illumination might also impact PLT function . The procedure creates a similar situation to cells challenged by stress, triggering the activation of a variety of protein kinases, called stress‐activated kinases, such as p38MAPK, ERK, and c‐JUN .…”
Section: Discussionmentioning
confidence: 99%
“…RF-PI treatment targets the RNA or DNA of pathogens; however, as PLTs contain mRNA this illumination might also impact PLT function. [28][29][30][31] The procedure creates a similar situation to cells challenged by stress, triggering the activation of a variety of protein kinases, called stressactivated kinases, such as p38MAPK, ERK, and c-JUN. [32][33][34] Immunoblot analyses in this study using the RF-PI system monitored the phosphorylated levels of protein kinases and showed that p38MAPK, ERK, and MLCK were significantly activated in PLTs during storage after RF-PI treatment.…”
Section: Discussionmentioning
confidence: 99%
“…reported that complete inactivation of all bacterial species with CFU concentrations of 100 and 1000 per platelet product throughout storage or investigation period. [25] Goodrich et al . spiked 20–100 CFU per platelet product and demonstrated that riboflavin and UV light treatment was 91% effective against broad spectrum of bacteria.…”
Section: Discussionmentioning
confidence: 99%